2017
DOI: 10.1177/2309499017717869
|View full text |Cite
|
Sign up to set email alerts
|

Total hip arthroplasty after failed osteosynthesis of proximal femoral fractures: Revision and mortality of 80 patients

Abstract: THA was associated with an increased surgical revision rate, but hip dislocation was documented only once. In most cases, a standard implant with a large 36-mm femoral head size was sufficient. Uncemented revision stem revealed significantly higher number of revisions-compared to standard cemented or uncemented stem. One-year mortality was lower than expected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 31 publications
1
14
1
3
Order By: Relevance
“…5,22,23 Use of larger head size can help to reduce postoperative dislocation. 24 The smaller average pelvic size in our cohort of population does not permit femoral head more than 28 mm.…”
Section: Discussionmentioning
confidence: 64%
“…5,22,23 Use of larger head size can help to reduce postoperative dislocation. 24 The smaller average pelvic size in our cohort of population does not permit femoral head more than 28 mm.…”
Section: Discussionmentioning
confidence: 64%
“…Reaming acetabular cartilage judiciously; avoiding forceful component impaction; considering screws augmentation [17,37] Greater trochanter reattachment Contoured plating, tension band wiring and trochanter claw plate with wiring [11,30,35,36,46] instead, augmentation of the fixation with screws should be considered [17,37]. A separated greater trochanter, commonly seen in patients subjected to IT fixation failure, usually causes pain and limping and even affects abductor function [31,49].…”
Section: Technical Challenges and Considerationsmentioning
confidence: 99%
“…Additionally, evidence has revealed that a higher dislocation rate of hip arthroplasty is correlated with displaced fracture of the greater trochanter [31]. Three methods for fixation of the greater trochanter have been mentioned: contoured plating, tension band wiring, and trochanter claw plating with wiring [11,30,31,35,36,46]. In a retrospective study of 16 failed IT fixations, all patients received surgery with HA and the cable-grip system.…”
Section: Technical Challenges and Considerationsmentioning
confidence: 99%
See 2 more Smart Citations